Re-enchanting the world : Maya Protestantism in the Guatemalan highlands - Samson, C. Mathews, 1960- (Contemporary American Indian studies., 2007)
In considering the interplay between contemporary Protestant practice and native cultural traditions among Maya evangelicals, this work documents the processes whereby some Maya have converted to different forms of Christianity and the ways in which the Maya are incorporating Christianity for their own purposes.